1986
DOI: 10.1007/bf00714993
|View full text |Cite
|
Sign up to set email alerts
|

Vascular fluid shifts and endocrine responses to exercise in the heat

Abstract: This study examines the relationships between vascular changes and endocrine responses to prolonged exercise in the heat, associated with dehydration and rehydration by fluids of different osmolarity. Five subjects were exposed, in a 34 degrees C environment for 4 h of intermittent exercise on a cycle ergometer at 85 +/- 12 Watts (SD). Fluid regulatory hormones and cortisol were analysed in 3 experimental sessions: one without any fluid supplement (NO FLUID), and two with progressive rehydration, either by spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 37 publications
3
49
1
Order By: Relevance
“…We emphasise that the present findings were obtained using permissive dehydration to a modest level of hypohydration (~1.8%); a level at which additional fluidregulatory stimuli are already induced (Table 2) (Brandenberger et al 1986;Brandenberger et al 1989;McConell et al 1997) and thirst becomes stimulated to limit excessive dehydration (Engell et al 1987;Sawka et al 1987;Nadel et al 1993). Whether greater dehydration and/or a longer acclimation regime would be more beneficial or detrimental is unknown and requires further investigation, but if exercise training is an important component of the acclimation then the training impulse would become reduced (especially if using the controlled hyperthermic regime).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…We emphasise that the present findings were obtained using permissive dehydration to a modest level of hypohydration (~1.8%); a level at which additional fluidregulatory stimuli are already induced (Table 2) (Brandenberger et al 1986;Brandenberger et al 1989;McConell et al 1997) and thirst becomes stimulated to limit excessive dehydration (Engell et al 1987;Sawka et al 1987;Nadel et al 1993). Whether greater dehydration and/or a longer acclimation regime would be more beneficial or detrimental is unknown and requires further investigation, but if exercise training is an important component of the acclimation then the training impulse would become reduced (especially if using the controlled hyperthermic regime).…”
Section: Discussionmentioning
confidence: 76%
“…The neuroendocrine system regulates the volume and composition of plasma volume and intracellular fluid of red blood cells, whose essential components for the retention of  Na and water are the renin-angiotensin-aldosterone system and AVP (Brandenberger et al 1986). In the present study, after 90-min exercise [aldo] p increased across DEH bouts in contrast, to a limited response after EUH acclimation and this difference was significant.…”
Section: Fluid Regulatory Hormones and Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some factors such as stage in the menstrual cycle, oral contraceptive regimes (Bonen et al 1991;Murphy et al 1990) or state of hydration (Brandenberger et al 1986) may explain this disagreement. However, our results are in line with previous ®ndings in men (Remes et al 1979).…”
Section: Discussionmentioning
confidence: 96%
“…Follenius et al (1989) have shown that the effects of ingesting isotonic solutions on AVP were similar to those of water. Brandenberger (1986) also showed that AVP responses increased with exercise and decreased with fluid intake.…”
Section: Discussionmentioning
confidence: 91%